INOVASI PEMBELAJARAN LOMPAT TINGGI : MENINGKATKAN PRESTASI SISWA KELAS V MELALUI PERMAINAN LOMPAT TALI - Miftachul A’la; Liska Sukiyandari (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
Physical education plays a crucial role in the development of students' physical skills, including high jump. However, many students face difficulties in achieving optimal results in this sport. This study aims to improve the learning outcomes of high jump in fifth-grade students at SDN Mendongan Sumowono through a play-based method using cardboard. The subjects of the study consisted of 31 students. The method used is classroom action research conducted in two cycles. The instrument used is a high jump performance test. The results show that the average score of students in pre-action activities was 69.56 with a completeness percentage of 32.36%. In cycle I, the average score increased to 73.39 with a completeness percentage of 64.52%. After proceeding to cycle II, the average score of students further increased to 77.22 with a completeness percentage of 90.32%. These results indicate that the cardboard jumping game method is effective in enhancing students' high jump skills. The research was stopped in cycle II as the set target had been achieved.